MENGELOLA ORGANISASI INFORMAL DI SEKOLAH - Herawati, Reni (Jurnal Ilmiah Guru Caraka Olah Pikir Edukatif, 2015)
School organization can be viewed from two dimensions: formal and f:zformal. These two kinds of organization have different structures. School principals and teachers are aware of and able to accept the existence of formal structure within a school, but few of them understand that there are informal structures in a school. Informal structure is a kind of 'hidden energy' that must be realized, managed and mobilized in order to provide a positive role in providing good education management. School principals should understand how to manage the informal structures in order to be empowered positively and support the implementation of a f ormal organization.